If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + 1 + 3 = 6 + 3k Reorder the terms: 1 + 3 + k = 6 + 3k Combine like terms: 1 + 3 = 4 4 + k = 6 + 3k Solving 4 + k = 6 + 3k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3k' to each side of the equation. 4 + k + -3k = 6 + 3k + -3k Combine like terms: k + -3k = -2k 4 + -2k = 6 + 3k + -3k Combine like terms: 3k + -3k = 0 4 + -2k = 6 + 0 4 + -2k = 6 Add '-4' to each side of the equation. 4 + -4 + -2k = 6 + -4 Combine like terms: 4 + -4 = 0 0 + -2k = 6 + -4 -2k = 6 + -4 Combine like terms: 6 + -4 = 2 -2k = 2 Divide each side by '-2'. k = -1 Simplifying k = -1
| -3n-5n=o | | r/2-8=-3 | | 1(x-3)=9(2-3) | | --8(1+4x)-4=-236 | | 29+13x=32 | | 2*t^2-14*t+3=3 | | -4+6=42 | | 140=4(1-4x+8) | | 2(4-0.3h)=3 | | X^3y^6=27 | | 5(x-2)=-15 | | 400-5P=148+37P | | 3(2x+7)=20 | | 7h+9-8h=-32 | | 5p=-10+8p | | 2(b+1)-36=3(3+26) | | -3x+8+2x=2 | | 9+k=11 | | .20*6=x | | 4x+2y=140 | | -94=2-2(7x-8) | | 2m+1*3+8=11+16m | | -7x+4+2x=-6 | | 6x-10+12=0 | | .20*x=1.20 | | 4y-9=2y+7 | | 5x^2+14x+8= | | -7x+4+2x=-7 | | n^2+5*n+7=7 | | 3q-16q=7+(-8p-3) | | 3/4(1p+12)=1/2(1p-6) | | y-5=3-9(y+2) |